Sustainable Urban Water Management: Reuse, Recycling and Climate-Resilient Strategies - Solomon E. Shaibu; Peter O. Adigun; Nnamso D. Ibuotenang (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The pressures of urbanization, climate change, and resource scarcity demand sustainable urban water management practices to ensure long-term water security. This study explores integrated approaches, including water reuse, recycling, and climate-resilient strategies, to address these challenges effectively. Innovative solutions such as constructed wetlands, membrane bioreactors, and nanotechnology-driven water purification systems are identified as key advancements in optimizing water resources. These technologies not only improve water quality but also contribute to reducing environmental impacts. Additionally, the study emphasizes the role of green infrastructure, such as permeable pavements and rain gardens, in managing stormwater and enhancing urban resilience. Decentralized wastewater treatment systems are highlighted as crucial for reducing reliance on centralized infrastructure, offering flexibility and efficiency in densely populated urban areas. The integration of these technologies with community-driven water conservation efforts can create a robust framework for sustainable urban development. By reviewing current challenges and emerging technologies, the study underscores the importance of a holistic approach to urban water management. This includes fostering cross-sectoral collaboration, policy support, and public awareness to build climate-resilient and resource-efficient cities. Ultimately, adopting innovative and sustainable practices is imperative for addressing the growing demands on urban water systems in an era of global change.
Keywords: Sustainable Urban Water Management; Water Reuse and Recycling; Climate-Resilient Strategies; Nanotechnology in Water Treatment; Green Infrastructure